Restoration of mixed forest : effects of fencing, site preparation and distance to existing mixed forest on planted European beech and natural tree regeneration - Szydło, Mateusz (SLU/Southern Swedish Forest Research Centre, 2017)
During restoration of mixed forest from mono-specific spruce forest there is a great need for knowledge of the extent to which proximity to other mixed forest affects regeneration results and diversity of tree and shrub layers. There is also lack of knowledge of what fencing means for the regeneration of individual species, as well as how mechanical site preparation (MSP) influences both planted and naturally regenerated plants. Mixed forests of pine (Pinus sylvestris), beech (Fagus sylvatica) and other deciduous species are valuable for nature conservation and recreation in Southern Sweden and other parts of Northern Europe. The purpose of this work was to assess the effects of inverted soil scarification, fencing and proximity to mixed forest in planted beech and natural regeneration of Scots pine as well as other tree species. The hypothesis of the work was that beech and pine growth benefits from site preparation and fencing as well as that natural regeneration of pine also benefits from site preparation and the proximity of existing seed trees in older mixed forest. Data collection took place in a field experiment established in 2011 in Sveaskogs ecopark Raslången in northern Scania (Skåne). During winter in 2017 an inventory of planted beech trees in the experiment was made concerning height and potential damages. In the same way all natural regeneration of Scots pine and other tree species were measured. Planted beech’s height was found to be positively affected by site preparation, saplings were on average about twenty centimeters taller, as well as natural regeneration of both Scots pine, where the regeneration was doubled comparing to non-preparated sites, and goat willow (Salix caprea) where regeneration turned out to be over six times more frequent. Fencing was shown to be a crucial aspect especially for Scots pine regeneration as the species experienced a high level of browsing in unfenced plots. The distance to the nearest mixed forest turned out not to have notable influence on the magnitude of natural regeneration, which was dominated by birch (Betula spp., 53% of all naturally regenerated trees). Birch, as well as goat willow and pine are pioneer species which find it easy to establish on most of the sites. Birch however is more universal and can grow as good on not-prepared site as on the prepared. In the coming years, an early thinning in birch and goat willow seems to be necessary due to its ability to overgrow species that develop on the same site. The recommendation for the experiment should be promoting pine development, as a light demanding species it requires space to grow. The condition of the fence should be taken care of as well because it favors the development of both beech and pine, two main species of the future mixed forest.